PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MIND MAP TERHADAP HASIL BELAJAR BIOLOGI - Ni Kadek Ayu Sukadewi; N Putri Sumaryani (FPMIPA IKIP PGRI Bali, 2016)
The Effect of Talking Stick Learning Model Assisted by Mind Map on Learning Outcomes Biology The role of educators as an information center slowly shifting to become a facilitator, mediator, and friends to share information so as to materialize the success rate of higher learning. However, the fact that the learning outcomes are achieved biology learners still low. The purpose of the study was to determine the effect talking stick-assisted learning model mind map to the learning outcomes of students of class X biology IPA at SMAN 1 Abiansemal the academic year 2013/2014. type of quasi-experimental research (quasi experiment). The independent variables were included talking stick-assisted learning model mind map that is worn on the experimental group and learning by conventional methods imposed in the control group. The dependent variable in this study is the result of study biology. The data required in the form of biological learning outcomes obtained using instruments such as biology achievement test, then the data were analyzed by t-test. The analysis showed t count = 3.748 and t table = 1.980 means that t count> t-table can be interpreted reject Ho and accept H1, which states that there is influence learning model talking stick aided mind map on learning outcomes biology learners class IPA X SMAN 1 Abiansemal the academic year 2013/2014.